A Newly Developed Rate Analysis Method for a Single Shale Gas Well. Issue 3 (June 2015) - Zhang, Xiaotao; Jiang, Xin; Yang, Jiyuan; Chen, Man
With a rapid growth in the shale gas industry, the development of a corresponding reservoir engineering theory was promptly needed. The decline laws for shale gas reservoirs differed dramatically from the traditional methods designed for conventional gas reservoirs. This paper summarized and compared the characteristics, assumptions and limitations of world's widely-used rate decline analysis methods for shale gas. Also, based on the field situations of gas wells, a rate decline analysis method, which is compatible with shale gas production, was presented. The method was validated by comparing its results with production data of shale gas wells in the Sichuan Basin. The advantage of the method, which is proposed in this study, is that it is not biased toward any gas production regime or WHP. By taking into account the different production regimes, it could provide a better analysis of the rate behavior characteristics in shale gas wells.